Famílias acolhedoras: um estudo comparativo - Camargo, Vera Lúcia Kelemen (2007)
In this work, we carry through a comparative and qualitative study on three programs of Foster Families, in the State of São Paulo, Brazil. The purpose of the research was to know, in order to delineate and compare, the profiles of the cited programs, by highlighting the genesis, the peculiarity and the comprehension of each one of them. Moreover, the survey aimed to raise the chances and the difficulties lived during the process of implementation, implantation and functioning of the programs. The research reveals that there is a diversity of proposals of programs of Foster Families and there are also some elementary aspects so that those programs may work minimally. The absence of homogeneity in the way of operating these programs, as well as in the way of defining criteria for their effective unctioning, does not configure negative aspects for the existence and permanence of these initiatives. Although divergent, in some ccasions, they contribute (respecting the specifications of each program) to improve the quality of the attendance to the necessities of children and/or adolescents who are moved away from the cohabitation with their families of origin. Thus, what justifies the existence of these programs, at first, is the possibility of offering humanized and individualized conditions of attendance to the children and adolescents who are under situations of vulnerability and/or imminent social risk, as well as fostering that is similar, in the positive aspects, to the ones they received from their families of origin, guaranteeing them the right to family and community life